Prediction of rain attenuation on earth-to-satellite link using rain rate measurement with various integration times - Momin, Mullah; Alam, Md Moktarul; Mahfuz, M. M. Hasan; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Badron, Khairayu (IEEE, 2021)
Frequency spectrum for satellite communication systems is moving towards Ka- and V-bands, the performance of which is severely degraded by rain attenuation, especially in tropical regions. ITU-R 618-13 and few other researchers proposed a complete method to predict rain attenuation at any desired frequency. All prediction models require rain rate at 0.01% of time occurrence measured by rain gauge with 1-min integration time. Few measurements of rain attenuation in Malaysia reported that ITU-R 618-13 model underestimated the measurement at Ku-band. However, ITU-R recommends that rain intensity must be measured with one-minute integration time or less in order to predict rain effects on microwave propagation. All Recommendations and prediction methods are reported and presented based on rain rate measured with 1-minute integration time. This paper presents the statistical distributions of rain rate measured in Malaysia with 10-sec, 20-sec, 30-sec, 1-min and 2-min integration times. ITU-R P.618-13 prediction method is used to estimate earth-to- satellite link’s rain attenuation using measured rain rate with 10-sec, 20-sec, 30-sec, 1-min and 2-min integration times and compared with measurements.